India's development cooperation in Africa: The case of "Solar Mamas" who bring light - Veda Vaidyanathan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper examines multiple facets of New Delhi's development cooperation with countries in Africa and argues that grassroots organizations in India that find innovative, low-cost technological solutions to developmental challenges can help governments and multilateral agencies craft inclusive, sustainable policies. The aim of this paper is threefold. First, to understand the major actors, instruments, themes, and mechanisms that make up India's Development cooperation towards countries in Africa and how these usher in a new dimension of 'South-South cooperation'. Second, the paper will explore the role of grassroots organizations that have found localized solutions in India that then export their learnings to other geographies and how they craft a unique role for themselves in India's broader development cooperation framework. To explore this idea further, the paper will utilize the case study of a community-based grassroots organization, Barefoot College, Tilonia, founded by Sanjit Bunker Roy in 1972, and its solar programme. The college trains women from unelectrified, remote communities to become solar engineers who then return to their rural villages with the ability to harness solar power, earning them the title of 'Solar Mamas'. Third, this paper argues that the uneven, fragmented Indian experience of designing development assistance programmes provides an important non-western perspective that can help decision makers craft policies for an era beyond aid.
Keywords: F50; O30; O10; Q42; 330; India; Africa; development cooperation; sustainability; technology; innovation